Transport barrier in 5D gyrokinetic flux-driven simulations. (1st December 2022) - Lo-Cascio, G.; Gravier, E.; Réveillé, T.; Lesur, M.; Sarazin, Y.; Garbet, X.; Vermare, L.; Lim, K.; Guillevic, A.; Grandgirard, V.
Abstract: Two ways for producing a transport barrier through strong shear of the E × B poloidal flow have been investigated using GYSELA gyrokinetic simulations in a flux-driven regime. The first one uses an external poloidal momentum (i.e. vorticity) source that locally polarizes the plasma, and the second one enforces a locally steep density profile that also stabilizes the ion temperature gradient (ITG) instability modes linearly. Both cases show a very low local turbulent heat diffusivity coefficient χ T turb and a slight increase in core pressure when a threshold of ω E × B ≈ γ ¯ lin (respectively the E × B shear rate and average linear growth rate of ITG) is reached, validating previous numerical results. This pressure increase and χ T turb quench are the signs of a transport barrier formation. This behaviour is the result of a reduced turbulence intensity which strongly correlates with the shearing of turbulent structures as evidenced by a reduction of the auto-correlation length of potential fluctuations as well as an intensity reduction of the k θ spectrum. Moreover, a small shift towards smaller poloidal wavenumber is observed in the vorticity source region which could be linked to a tilt of the turbulent structures in the poloidal direction.